Sustainable leadership among financial managers in Spain: A gender issue - Bulmer, Elene; Zamarrón, Ivan; Yañez-Araque, Benito (Edelweiss Applied Science and Technology, 2024)
Finance plays a key role in supporting sustainable companies, thereby contributing, and supporting the transition towards a low carbon and circular economy. At the strategic level, finance can aid companies make decisions regarding the trade-offs between their sustainable goals. Therefore, key players in this respect are finance managers who need to take decisions regarding the latter. This study analyzed the level of sustainable leadership among financial managers in Spain. A total of 131 senior financial managers (106 men and 25 women), from various sectors in Spanish companies (a multi-sector study), responded to two scales: the Honeybee Sustainable Leadership Scale (focusing on stakeholder orientation and a vision of social and shared leadership) and the Locust Leadership Scale (primarily centered on achieving short-term profits at any cost). A descriptive analysis of the sample was conducted. The t-test was applied for comparing means and the Mann-Whitney U test statistical technique was used under conditions where the assumptions of normality and homogeneity of variance were violated. In the hypothesis testing, a significance level of p<0.05 was employed. The main finding was that female financial managers scored significantly higher on the Honeybee Leadership Scale compared to their male counterparts, signifying that female presence is key to sustainable leadership. Therefore, including women in higher corporate-level positions would contribute to a more sustainable approach in management. Furthermore, it was also found that the organizations in which the financial managers worked tended to undertake a hybrid approach to sustainable leadership. Most companies undertook a hybrid perspective incorporating elements of both diametrically opposed bee and locust leadership philosophies.